2012
DOI: 10.3390/su4030394
|View full text |Cite
|
Sign up to set email alerts
|

The Tragedy of Maldistribution: Climate, Sustainability, and Equity

Abstract: This essay is an initial exploration of the dimensions of the equity/sustainability linkage from the perspective of public goods analysis. Sustainability requires an abundance of public goods. Where these commons lack governance, sustainability is at risk. Equity is a critical component of sustainability that can itself be viewed as a public good, subject to deterioration (maldistribution) when left ungoverned. As is the case for so many forms of environmental degradation, the private benefits of maldistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
(68 reference statements)
0
12
1
Order By: Relevance
“…Besides, the population growth seems to lead to lower volumes of industrial solid wastes, perhaps to be explained by the relatively limited expansion of new industrial construction in the metropolis in recent years. The volume in new patent application also has a certain influence on the generated volume of industrial solid wastes, which is contradictory to what is found in some earlier literature [47,48]. This is evidence that technological progress has two different possible consequences for environmental pollution: it either relieves environmental pressure or intensifies it.…”
Section: Discussioncontrasting
confidence: 56%
“…Besides, the population growth seems to lead to lower volumes of industrial solid wastes, perhaps to be explained by the relatively limited expansion of new industrial construction in the metropolis in recent years. The volume in new patent application also has a certain influence on the generated volume of industrial solid wastes, which is contradictory to what is found in some earlier literature [47,48]. This is evidence that technological progress has two different possible consequences for environmental pollution: it either relieves environmental pressure or intensifies it.…”
Section: Discussioncontrasting
confidence: 56%
“…The environmental Kuznets curve (EKC) hypothesis has the main maxim that there is the existence of an inverted U-shaped curve between environmental pollution and economic development (Stanton, 2012). It also maintains that at early stages of economic growth, environmental degradation and pollution will increase at an increasing rate.…”
Section: Introductionmentioning
confidence: 99%
“…Spillemaeckers et al (2004) may be difficult to evaluate. However, some forestry related jobs may be more accident prone (e.g.…”
Section: Accidents and Work-related Diseasesmentioning
confidence: 99%
“…However, indirect work-related health issues such as cancer and respiratory diseases may have been underestimated (Hämäläinen et al 2009). Spillemaeckers et al (2004) proposed a quantitative health and safety indicator to be based on statistical sources and list several indicators (e.g. training, auditing and formal work policy) to measure "occupational health and safety".…”
Section: Accidents and Work-related Diseasesmentioning
confidence: 99%